4CPS-113 Experience with braf and mek inhibitors in the treatment of metastasic melanoma in a third-level university hospital. (2nd March 2018) - Escoda, A Comes; Castells, G; Carcelero, E; Riu, G
Abstract : Background: The MAPK-pathway is a signal transduction cascade involved in the uncontrolled proliferation of many cancers. Mutations that activate these pathways occur in more than 90% of melanomas. This has led to the development of dabrafenib and vemurafenib (target V600E/K BRAF), and trametinib and cobimetinib (target MEK1/2). Purpose: To describe our experience in terms of effectiveness and safety in the use of BRAF/MEK inhibitors in metastatic melanoma (MM) with an activated MAPK-pathway. Material and methods: Retrospective observational study including patients with MM who received treatment with dabrafenib, trametinib, vemurafenib and/or cobimetinib. Clinical data were collected from electronic patients' medical records, from the treatment prescription until May 2017, including: age, sex, ECOG, prior immunotherapy and chemotherapy lines, toxicity and treatment discontinuation. Response was measured as the time period from the start of treatment to the date of documentation of progression or lost to follow-up (PFS). Results: This study comprised 62 BRAF mutated patients (48.39% males) with a median age of 55 years (18–89) and a medium ECOG of 1 (47%). 16.13% received prior immunotherapy. Forty-seven per cent of patients were treated with dabrafenib +trametinib, 16% with vemurafenib +cobimetinib, 13% with dabrafenib, 11% with vemurafenib and 13% were combinations. Sixty-eight per cent of BRAF/MEK inhibitors were prescribed as a first-line treatment, 26% as second line and 3% as a third or more lines. Adverse events (AE) reported were: skin disorders (80%), elevated liver enzymes (64%), asthaenia/myalgia (59%), gastrointestinal disorders (55%), fever (36%), anaemia/neutropenia (23%) and ocular disorders (22%). Most of the AE were classified as grade 1–2 according to the Common Terminology Criteria for Adverse Events version 4.0. Fifty-two per cent of treatment discontinuations were due to disease progression, 22.58% toxicity and 8.06% death. Data of median PFS are available for 54 patients: 5.8 months for dabrafenib, 5.4 months for dabrafenib +trametinib, 1.34 months for vemurafenib and 7.48 months for vemurafenib +cobimetinib. These results are inferior compared with the pivotal studies. Conclusion: The majority of BRAF-mutated patients in our hospital with MM began with BRAF/MEK inhibitors as first-line treatment. AE were frequent, but manageable. PFS was lower than the pivotal studies. However, we need information on more patients to confirm these results. No conflict of interest